A holistic study of factors governing small and medium enterprises in India. (12th July 2021) - Bagodi, Virupaxi; Raravi, Prasannna P.
Abstract : Purpose: The purpose of this paper is to identify the input, process and output factors (along with their manifest variables) of small and medium enterprises (SMEs), and to establish cause and effect relationships amongst the factors and sub-factors. Systems thinking, a holistic approach, is used to carry out qualitative analysis of the feedback loops. Design/methodology/approach: A well-structured questionnaire was developed to gather the relevant data to identify the factors affecting the performance of SMEs in a holistic manner. A total of 150 responses were collected during November 2015–March 2016. Factor analysis and path analysis were used to establish causal relationships between input, process and output factors. The systems thinking approach has been used for qualitative analysis. Findings: Feedback loops have been identified amongst input-process-output-input factors and amongst sub-factors. They enabled authors to infer that the managers/owners of SMEs are systems thinkers, if not completely, at least partially. Six negative feedback loops and one positive feedback loop prevail. System behaviour arises out of the interaction of positive and negative feedback loops; it appears that in the long-run, the SMEs attain their target levels. The following inferences are drawn: circular relationships are identified amongst input, processes and organisational performance (OP), modern management tools such as just in times, Kanban have long-term benefits and are perceived as ineffective by small enterprises and formal financing and functional transparency enhances OP. Originality/value: Systems thinking, a holistic approach, has been used to study the effect of input, process and output factors on one another. Such studies are sparse, especially, in the Indian context. Many studies have been conducted to study the effect of input and of processes on performance such as innovation, information technology, human resource, technology, government regulation on performance of SMEs in a silo but, rarely all together. The qualitative analysis adds value to the research. Many of the outcomes of the research have been largely discussed in Indian print media which indicates the pragmatic approach of the research.